Literature Review: Pengaruh Pengungkapan Manajemen Risiko Perusahaan Terhadap Nilai Perusahaan - Wulandari Wulandari; Helfina Meisarah; Sri Mulyana; Arsyadona Arsyadona (Trending: Jurnal Manajemen dan Ekonomi, 2024)
This study aims to understand more about how enterprise risk management disclosure can affect firm value. The research method used is qualitative research with a literature review approach to structurally discuss previous research articles. In this study, the literature used is published from 2017-2023, which can be accessed in full-text PDF format through Google Scholar using the Publish or Perish (PoP) application. The results showed that risk management disclosure has a positive and significant influence on firm value. This means that the more enterprise risk management disclosure items published by the company, the higher the value of the company. The extent of disclosure of information regarding risk management is one of the factors that investors consider before making a decision to buy shares, in addition to the company's ability to generate profits in good condition.